2002
DOI: 10.1093/swr/26.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic pride, biculturalism, and drug use norms of urban American Indian adolescents

Abstract: This study examines how strength of ethnic identity, multiethnic identity, and other indicators of biculturalism relate to the drug use norms of urban American Indian middle school students. The article distinguishes categories of norms that may affect drug use. Regression analysis of self-reports by 434 American Indian seventh graders attending middle schools in a large southwestern U.S. city indicated that students who had a more intense sense of ethnic pride adhered more strongly to certain antidrug norms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 36 publications
4
79
1
Order By: Relevance
“…The ecological risk and protective process model is reflected in research focused in the etiologies of disease (Link & Phelan, 1995) and mental illness and violence (Hiday, 1995), which argue that individually based risk factors must be contextualized in order to understand the development of adverse health outcomes. Finally, contemporary resiliency theorists also emphasize the importance of a strong, positive cultural/ethnic identity (ethnic pride) as a protective factor, which has been supported in recent research on drug use and American Indian youth (Kulis, Napoli, & Marsiglia, 2002).…”
Section: Resiliency Theorymentioning
confidence: 97%
See 1 more Smart Citation
“…The ecological risk and protective process model is reflected in research focused in the etiologies of disease (Link & Phelan, 1995) and mental illness and violence (Hiday, 1995), which argue that individually based risk factors must be contextualized in order to understand the development of adverse health outcomes. Finally, contemporary resiliency theorists also emphasize the importance of a strong, positive cultural/ethnic identity (ethnic pride) as a protective factor, which has been supported in recent research on drug use and American Indian youth (Kulis, Napoli, & Marsiglia, 2002).…”
Section: Resiliency Theorymentioning
confidence: 97%
“…In addition to the protective effect of ethnic pride (Kulis et al, 2002), a developing body of literature has emphasized the protective effect of immediate and extended family members on drug use and American Indian youth. For example, two focus group studies examined the protective impact of siblings and cousins on the drug use of Southwestern American Indian middle school students Waller et al, 2003).…”
Section: Resiliency Theorymentioning
confidence: 99%
“…Specifi cally, American Indian youth appear to be at a heightened risk for consequences of alcohol misuse (Kulis et al, 2002). In one study, approximately one third of American Indian youth began to use alcohol by age 11 (Mail, 1995), and the average age at substance use initiation among American Indian youth is younger than what is found in other ethnic groups .…”
Section: T He Use and Misuse Of Alcohol Is A Major Problem Among Youtmentioning
confidence: 99%
“…The main objectives in the analysis of the American Indian youth subsample was to (1) identify the prevalence, age of initiation, and frequency of drug use; (2) identify the degree of exposure to drugs; and (3) identify how drug use outcomes were mediated by ethnic identity, age, and gender. Based on this analysis, Kulis, Napoli, and Marsiglia (2002) found that American Indian students who had a more intense sense of ethnic pride adhered more strongly to antidrug norms than those who did not. This suggests that ethnic pride for American Indian youth may serve as a protective factor against drug use.…”
Section: Stage 1: Survey Data Analysismentioning
confidence: 98%